Diseño de molde de inyección para la fabricación de una direccional LED (2017)
The design of the mold for directional led type, started from a necessity by the company MATROMOL S.A.S, which proposes technical and geometric characteristics to obtain the desired product; Based on the proposed requirements, a prototype of the product is designed, which is presented and accepted by the company.